Liver Enzymes Correlation among Chronic Hepatitis C Patients with Virus Infection Fibrosis Progression - Aziz, Hassan A; Moosa, Esra Mohamed; Bari, Redwana; Ruz, Rasha Abu El (Medicine Today, 2018)
The main aim of the study is to identify the association between liver enzymes and virus infection fibrosis progression among the patients, suffering from HCV infection. The study has recruited 195 patients, and data has been gathered for a five years' period from January 2010 till March 2015. The laboratory analyses were conducted on the blood samples to evaluate the level of liver enzymes (ALT, AST, GGT). A slight increase in ALT levels was observed among the patients, who received treatment for HCV infection. The ALT level was estimated to be 48.04% for patients with negative PCR. There is no significant correlation between ALT levels and development of HCV, even when the serum levels of ALT are increased. The patients with negative or positive PCR were observed to have increased level of AST. A slight increase was observed in the negative HCV patients for mean GGT levels, as compared to the positive HCV patients. The hepatic enzymes depicted significant correlation with hepatitis infection. Medicine Today 2018 Vol.30(1): 11-15